Latex Allergy: Do we need to worry? - S. Garro, Laila; Giavina-Bianchi, Pedro (Revista Saúde & Diversidade, 2017)
Latex allergy is an important health problem in selected population groups, who are called risk groups. Health care workers constitute a risk group, particularly those working in laboratories, nursing, surgeries or anesthesia. The incidence of latex allergy increases with the degree of exposure. The clinical manifestations has great variability and can range from a skin rash to life-threatening reactions. Early recognition of symptoms can avoid severe reactions in the future. Primary preventive measures are the most effective way to reduce sensitization and are responsible for the great reduction in the number of cases at countries that have chosen to exclude latex from medical materials.